2018
DOI: 10.17755/esosder.320376
|View full text |Cite
|
Sign up to set email alerts
|

Depresyon, Anksi̇yete Ve Stres Ölçeği̇ (Dass-42) Li̇se Formu: Türkçe Geçerli̇k Ve Güveni̇rli̇ği̇

Abstract: Bu araştırmanın amacı, Lovibond ve Lovibond (1995) tarafından geliştirilen, Türkçe’ye uyarlaması Bilgel ve Bayram (2010) tarafından üniversite öğrencileri üzerinde yapılan Depresyon, Anksiyete ve Stres Ölçeğinin (DASS-42) lise öğrencileri için psikometrik özelliklerinin belirlenmesidir. Bu amaçla DASS-42, iki farklı lisede öğrenim gören toplam 913 öğrenciye uygulanmıştır. Ölçeğin geçerlik çalışması için doğrulayıcı faktör analizi yapılmıştır. Ölçeğin güvenirliği Cronbach’s Alfa katsayısı ve madde toplam korela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The scores obtained from the scale ranged between 0 and 42 for each sub-dimension. Depression, anxiety, and stress were categorized on the scale into normal, mild, moderate, severe, and highly severe (Akkuş Çutuk & Kaya, 2018). The Cronbach's alpha coefficient was found in the present study to be .95.…”
Section: Adolescent Psychological Resilience Scale (Aprs)mentioning
confidence: 49%
See 3 more Smart Citations
“…The scores obtained from the scale ranged between 0 and 42 for each sub-dimension. Depression, anxiety, and stress were categorized on the scale into normal, mild, moderate, severe, and highly severe (Akkuş Çutuk & Kaya, 2018). The Cronbach's alpha coefficient was found in the present study to be .95.…”
Section: Adolescent Psychological Resilience Scale (Aprs)mentioning
confidence: 49%
“…Both the original and this study found positive and moderately significant correlations between resilience and school resilience scores. Besides, the original scale used the concept of depressive symptoms, while this study used the Depression, Anxiety, and Stress Scale-High School Form (DASS-42) (Akkuş Çutuk & Kaya, 2018). A moderately significant negative correlation was found between these variables and school resilience in the original scale and this study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Validity and reliability studies of the scale were carried out by Akkuş Çutuk and Kaya (2018) so that high school students can make self-assessments related to their depression, anxiety, and stress levels (Akkuş Çutuk and Kaya, 2018). The instruments include 42 items and 3 factors: depression (3, 5, 10, 13, 16, 17, 21, 24, 26, 31, 34, 37, 38, 42), anxiety (2, 4, 7, 9, 15, 19, 20, 23, 25, 28, 30, 36, 40, 41) and stress (1,6,8,11,12,14,18,22,27,29,32,33,35,39).…”
Section: Depression Anxiety and Stress Scale (Dass-42) High School Formmentioning
confidence: 99%